Faktor Risiko Babi yang Diumbar dan Pakan Mentah Mempertinggi Prevalensi Sistiserkosis (RISK FACTOR OF FEE-RANGE HUSBANDRY AND RAW PORK FEED INCEASE THE PREVALENCE OF CYSTICERCOSIS) - Assa, Inriyanti; Satrija, Fadjar; Lukman, Denny Widaya; Dharmawan, Nyoman Sadra; Dorny, Pierre (Jurnal Veteriner, 2013)
The aims of this study were to determine the prevalence and risk factors of porcine cysticercosis. Thesurvey was carried out in eight districts of Jaya Wijaya, Papua and Jibama market, during October 2009to June 2011. A total of 111 pigs were tested serologically. Serum samples were tested for the presence ofcirculating parasite antigen using monoclonal antibody-based sandwich enzyme-linked immunosorbentassay (MoAb-ELISA). Forty five samples (40.54%) were found positive by MoAb-ELISA and the highestprevalence occurred from the District of Asolokobal (92.86%), followed by Musatfak (75%), Kurulu (65.22%),Bolakme (33.33%), Asologaima (31.82%), Hom-hom (18.18%), Hubikosi (14.29%), Jibama trade (14.29%),and the lowest prevalence from Wamena Kota is 5.88%. Free-range pig husbandry system (OR=4.63;P<0.01) and uncook pork feed (OR=3.65; P<0.05) were important risk factors for porcine cysticercosis. It istherefore necessary to anthropology approach about pig husbandry system and pattern of cook pork feed.
Keywords: risk factor, porcine cysticercosis, prevalence